2022
DOI: 10.1111/1365-2745.13865
|View full text |Cite
|
Sign up to set email alerts
|

Influence of species functional strategy on leaf stoichiometric responses to fertilizer in a Bornean heath forest

Abstract: The distribution of Bornean heath forest on white sand soils is believed to be due to element limitation and soil acidity. To determine the impact of both element limitation and soil acidity on tropical heath forest, we established a soil fertilization experiment to investigate the impact that increased soil N availability and reduced soil pH (using lime/CaCO3) had on a range of elements in tree leaves. We hypothesized that alterations in soil resource availability would cause changes in the tree leaf N:P rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…As we measured only wet inorganic N deposition and were unable to consider organic N and dry deposition (which can be equal to or exceed wet N deposition), it is likely that the total N deposition in our study site exceeds the critical load of 10-15 kg N ha −1 year −1 , that is proposed as potentially damaging to temperate forests [38]. This is relevant because heath forest, a forest typology widespread throughout the tropics, is possibly limited by soil N, similar to temperate forests [43,44]. Heath forest, thus, could have a critical load similar to temperate forests.…”
Section: Discussionmentioning
confidence: 92%
“…As we measured only wet inorganic N deposition and were unable to consider organic N and dry deposition (which can be equal to or exceed wet N deposition), it is likely that the total N deposition in our study site exceeds the critical load of 10-15 kg N ha −1 year −1 , that is proposed as potentially damaging to temperate forests [38]. This is relevant because heath forest, a forest typology widespread throughout the tropics, is possibly limited by soil N, similar to temperate forests [43,44]. Heath forest, thus, could have a critical load similar to temperate forests.…”
Section: Discussionmentioning
confidence: 92%
“…SLA is closely related to resource availability, such as nutrients, water, heat, and light (e.g., [ 69 71 ]). The relationship between SLA and nitrogen concentration depends on soil nutrition status, environmental factors, and plant species (e.g., [ 14 , 72 , 73 ]). In the current study, we found strong associations of SLA with N mass rather than N area (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 ), meaning that larger and thinner leaves had a lower N concentration at the base of the leaf area than smaller and thicker leaves. This reflects the trade-off between leaf growth and N investment [ 39 , 73 ]. Lower SLA is generally associated with higher natural resource efficiency, such as WUE and NUE, under stressful conditions and thus can be recognized as a strategy of phenotypic regulation [ 38 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term kerangas, derived from the language of the local Iban community, refers to the infertile nature of the soil that prevents rice from growing (Brunig 1974;Whitmore 1984). Kerangas forests occur on weathered coastal alluvium and sandstone which give rise to nutrient-poor and acidic soils (Wong and Kamariah 1999;Wong et al 2015a;Sellan 2019). The sandy soils are porous and have high permeability which results in welldrained soils (Brunig 1974;Ghazoul and Sheil 2010;Jaafar et al 2016;Adanan et al 2020).…”
Section: Heath Forest Formations In Borneomentioning
confidence: 99%